A 3D-printed cap with sideoptics for colonoscopy: a randomized ex vivo study - Walter, Benjamin M.; Hann, Alexander; Frank, Rena; Meining, Alexander (Endoscopy, 2017)
Background Adequate polyp detection is crucial to colonoscopy; however, detection can be impaired. In particular, flat polyps located behind folds or near the colonic flexures appear to be a problem. We present a cheap and easily adjustable 3D-printed tool to enhance the view of a standard colonoscope using additional commercially available sideoptics. Materials and methods A cap adjustable to a standard endoscope was printed by a 3 D printer and had two microcameras fixed to offer two additional views. Fourteen endoscopists performed one standard and one sideoptic-enhanced colonoscopy in a randomized order. Flat lesions were simulated in an endoscopy training model. Time for withdrawal was measured, along with the number of flat lesions detected.Results Withdrawal time did not differ significantly between standard and sideoptic-enhanced colonoscopy (329 vs. 389 seconds). The median number of detected flat lesions per endoscopic examination was significantly higher using the sideoptic tool (8 vs. 6.5; P = 0.001).Conclusions A 3D-printed sideoptic-enhanced cap including two microcameras may be a cheap, easy, and feasible add-on to improve adenoma detection rates in routine colonoscopy.